Perception and Preparedness of Medical Students Towards the Health Care Needs Of LGBTQIA+ Community: A Cross-Sectional Study in Vadodara, Western India - Lakhan LRK Kataria; Rohan J Kosambiya; Vankar GK; Balas Rohit N; Kritagnasinh N Vaghela (Medsci Publications, 2023)
Introduction: The legalization of LGBTQIA+ community will bring a new stream of patients and their specific issues to healthcare community. Despite getting their place in society, they face discrimination and stigma from healthcare professionals, which will roadblock them from accessing healthcare. This study aims to document the perception of upcoming healthcare providers towards the LGBTQIA+ community and their preparedness to address their healthcare needs. Methodology: A cross-sectional survey conducted among 299 final MBBS students and Interns during "Pride month" June, 2022. An investigator-designed, validated, pre-tested, semi-structured questionnaire using Google forms, documented sexual-orientation of participants and their existing knowledge, attitude and practice towards the healthcare needs of LGBTQIA+ community. Results: Total 299 participants were enrolled, having a Response Rate of 94.9% (315 total participants). Proportion of female and male was 44.8% and 54.8% as sex (biological) respectively and 54.5% of participants identified themselves as man and 44.8% as woman as gender. Awareness about LGBTQIA+ community was among 98.33% of the participants. Mean Knowledge, Attitude and Practice Scores were 18.4 +2.7, 80.5 +12.4 and 31.4 +5.9, respectively and were positively correlated to each other. Female participants scored significantly higher, statistically than male participants in knowledge, attitude and practice domains. Conclusion: Despite of good knowledge and positive attitude toward LGBTQIA+ people, pockets of ignorance and discomfort reside among medical undergraduates and interns.